A thorough experimental investigation on airfoil turbulence interaction noise - Alper Celik (Physics of Fluids, 2023)
This paper on airfoil turbulence interaction noise reveals the nature of the relation between the distortion type of turbulent structures and radiated far-field noise. The turbulence interaction phenomenon is explored through comprehensive simultaneous hot-wire, surface pressure, and far-field noise measurements. Two grid turbulence cases are utilized to examine the effect of the coherent structure's length scale compared to the airfoil's leading-edge radius. The results show that the turbulent structures with a size comparable to the leading-edge radius disperse into smaller three-dimensional structures, losing their spatial coherence in the vicinity of the stagnation point. In contrast, the structures with larger integral length scales distort into highly coherent two-dimensional structures, yielding an increase in the surface pressure fluctuation energy spectra and the chordwise extent of the affected area by the interaction phenomenon, which is found to be responsible for the increased levels of far-field noise. The turbulence characteristics of the flow far upstream of the stagnation point determine the unsteady loading behavior at the stagnation point yet have little influence on the unsteady loading of the full airfoil chord. The stagnation point velocity fluctuations manifest a strong link to the remainder of the airfoil chord, as well as the near-field hydrodynamic to far-field acoustic signal coherence, while demonstrating no communication with the surface pressure fluctuations at the stagnation point.